Sperm motility in chronic bacterial prostatitis - Dicky Moch Rizal, Dicky Moch Rizal (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2003)
Background: Male infertility is 40% couples problem in conceiving a child. One of the causes of male infertility that has not studied yet is chronic bacterial prostatitis (CBP). CBP can decrease sperm motility that affects potency of sperm in fertilizing the oocyte. Another effect of CBP is leucospermia as the unique phenomenon in male accessory gland infection (MAGI).Objectives: To describe and to obtain the relation between sperm motility in CBP and the other prostate dysfunction that is not included to CBP (non CBP).Methods: This study was analytic descriptive non experimental study. The-subjects were person having suffered from prostate dysfunction, including CBP and non CBP, in Infertility Clinic Permata Hati of DR. Sardjito hospital. Data were taken from expressed prostatic secretion (EPS) analyses and seminal fluid analyses from May 2001 until June 2002 (56 data), Variable that observed from seminal fluid analyses were sperm motility and leucocyte count per milliliter. Determination of the CBP case was based on leucocyte count per high power field (HPF) and the other characteristics (i.e : clumping leucocytes and lipid laden macrophage) of EPS analyses. Data was analyzed by descriptive frequency to show the distribution of sperm motility and leucospermia. Beside to notice the relation between prostate dysfunction and sperm motility, Chi-Square test was used to notice the relation between prostate dysfunction and leucospermia as well.Results: As much as 76.7% patients with CBP had sperm motility disruption in progressive linear and linear movement. Fifty percents patients with prostate dysfunction had sperm motility disruption in progressive linear and linear movement. Mean of sperm motility With progressive linear movement in CBP and prostate dysfunction non CBP were 18.65% and 22.58%. Mean of sperm motility with linear movement in CBP and prostate dysfunction non CBP were 38.79% and 46.83%. From the Chi-Square test we obtained the significant difference between sperm motility with progressive linear and linear movement of the sperm and prostate dysfunction. -Conclusions: Over a half of patients (76.7%) with CBP suffered from decreased sperm motility. CBP affected sperm motility.Key words: male infertility, sperm motility, chronic bacterial prostatitis, semen analysis, expressed prostatic secretion (EPS)